Effectiveness of Management Information System Applications in Increasing Zakat at the National Zakat Amil Agency - Moelyadi Moelyadi; Abdul Rahim A; Anisa Marseli; Syamsurizal Syamsurizal; Novi Yanti; Alhazar Rinaldi (Institut Agama Islam Sumatera Barat, 2024)
ZIS management at Baznas Padang Pariaman City before the creation of SIMBA was still done manually. This causes several problems, such as the process of receiving, recording, and distributing ZIS funds which are slow and inefficient. These problems can have an impact on decreasing public trust in Baznas Padang Pariaman City. To overcome these problems, Baznas Padang Pariaman developed the SIMBA application. This study uses a qualitative method approach. This research was conducted at the Padang Panjang City National Zakat Agency Office. The instrument used in this study was an interview. The data sources in this study were primary data and secondary data. Data analysis techniques in this study were data collection, data reduction, data presentation and data verification. Data validity techniques in this study were source triangulation, technical triangulation and time triangulation. The results of the study showed that the Baznas Management Information System Application (SIMBA) at the Padang Pariaman National Zakat Agency was very effective because the results of direct research on the use of the SIMBA application met the indicators of program understanding, target accuracy, timeliness, and achievement of goals, real change. The advantages of SIMBA are that it makes it easier to input data, such as Muzaki registration, zakat data recording, to issuing receipts. Zakat distribution becomes more targeted and transparent with data and information on zakat recipients, types of assistance, and the amount of assistance provided. Accurate and faster zakat management reports are carried out. Muzaki can easily access information about zakat management, including their zakat data, zakat recipients, and BAZNAS zakat programs. Increased productivity by automating tasks. Increased accuracy of zakat data and minimize errors.